„Sammlung Ogoleit”: Goethe, Faust, Bauer. - Nodzyńska, Ewa (In Gremium. Studies in History, Culture and Politics, 2016)
Sammlung Ogoleit”: Goethe, Faust, Bauer. ZIELONA GÓRA PART OF THE COLLECTION OF WILHELM OGOLEIT – A BOOK SELLER AND COLLECTOR FROM GORZÓW Landsberg, Richtstrasse 8. The bookshop under the sign “Buch-Kunst-u. Musikalienhandlung”. Almost for fifty years, from the end of the 19th century until the year 1945 the above address was well known to all the lovers of the classical German poetry. This was due to the book seller and collector Wilhelm Ogoleit (1869-1953) who was able to gather the biggest in Brandenburg collection of memorabilia of Goethe and Schiller thus creating a private museum of the remembrance of the great “prince poets” of Weimar. The walls of the eight rooms of the Gorzów town house were decorated with painting, drawings and prints with the portraits of both poets and people working in culture who belonged to their circle. The collected pieces of art were presenting the illustrations of the literary works and the landscapes of the places relating to the biographies of the Weimar poets and other celebrities. The cabinets were displaying precious medals and plaques, the tables and the cupboards were displaying sculptures, busts and brick-a-brack, all of them signed “Sammlung Ogoleit”. The most precious artifacts included the patinated plaster head of Goethe sculpted by Klothilde Bauer-Rothmüller. The book lover, whom the owner of the collection definitely was, could not miss the library of books, first editions, manuscripts and letters. Among them there were the autographs and dedications from the pen of Goethe and one of the few heirlooms later saved from the war: the Goethe guest book. Ogoleit, a fervent advocate of the Goethean spiritual science, was seeking the meaning of life in the “eternal toil” which was the development of his fascination with the Goethe age and the circle of the Weimar artists. He was enlarging his collection over the years and it comprised 8800 items in 1945. He arranged a museum in his private flat where he hosted many inhabitants of the town and the visitors: actors, academics and musicians. He was famous for ceremonial guided tours which were about declamation and storytelling of literature and the times of the flowering of German philosophy and literature in the circle of Weimar court at the end of the 17th century. His enthusiasm and services in disseminating the cult of the German prince poets were noticed and awarded with the commemorative “Goethe Medal”. He received the distinction awarded by Hindenburg on his 65th birthday in 1934. Ogoleit was developing his collection through antique shopping in many German cities, mainly in Weimar, but also through personal communication with the artists of his times. The highest number of works was acquired from the Munich painter and printmakers Karl Bauer who is the author of the oil portraits of Goethe, a number of the poet’s images in a variety of different graphic techniques and a portfolio of ink drawing illustrating Goethe’s “Faust”. The Ogoleit collection was scattered and dispersed as a result of war. The work of destruction was completed by the fire in July 1945 in which the premises of the bookshop, private museum and the collector’s house – the town house at Richstrasse 8, now General Sikorski street, went up in smoke. The fragments of the collection which survived until now are treasured in the Lubuskie Jan Dekert Museum in Gorzów Wielkopolski and in two libraries in Zielona Góra: the Norwid Voivodship and Municipal Public Library and the University of Zielona Góra Library which owns the collection of 448 works stamped with the characteristic words “Sammlung Ogoleit”.